Parenting styles and obsessive-compulsive symptoms in college students: the mediating role of perfectionism - Hu, Po; Liang, Pengwei; Liu, Xiaoyan; Ouyang, Yuting; Wang, Jianping (Frontiers in Psychiatry, 2023)
Obsessive-compulsive symptoms are most often seen in university students in their twenties, and have a serious impact on their physical and mental health. Previous research has shown that the more negative the parenting style, the more pronounced the individual's obsessive-compulsive symptoms. However, few studies have examined the mechanisms underlying this phenomenon. It has also been found that individual perfectionism is closely related to parenting style and individual obsessive-compulsive symptoms. Therefore, this study sought to examine the mediating role of perfectionism in the relationship between parenting styles and obsessive-compulsive symptoms, using university students as the study population. In total, 661 university students were enrolled in this study. The findings revealed that negative perfectionism mediated the relationship between negative parenting styles and obsessive-compulsive symptoms in university students. The results of this study suggest that perfectionism in college students is an important factor in the development of obsessive-compulsive symptoms in the context of negative parenting styles. This study provides further evidence of the mechanisms underlying the occurrence of obsessive-compulsive symptoms, and offers new ideas for interventions for OCD.